Cycling performance and cellfood - Djordjevic, S.; Milic, R. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Many supplements on the market today claim they can have a positive effect on adaptation/training process and sport performance. One of these is Cellfood (NuScience Corp., Lancaster, California, USA).The aim of our study was to evaluate the effect of Cellfood supplementation on the cycling performance during 5 weeks of training in the preparation period. Methods Subjects consisted of 16 highly trained male competition cyclists (1), age 24.9 ± 3.4 yr., body height (179.5 ± 6.2cm) and body mass (70.3 ± 3.5 kg). The primary mode of training was cycling 8 times per week (4 times aerobic, 3 times mixed aerobic + anaerobic and once per week speed-anaerobic type of training load). Testing Procedures After 15 min warm-up on their bicycle set up on a cycle ergometer (SpinTrainer - TechnoGymTM) cyclist proceeded with incremental test (initial load 150 watts (W), increase 20 W min-1 to volitional fatigue), (2,3). Heart rate, ventilatory and gas data were collected continuously during the test with Cosmed K4b2 portable device. Lactate samples (20µl) were analyzed on Eppendorf Ebio +. Measurements and Supplementation Procedure Cyclist were randomly divided in two groups: the first group (CF group) took 12 drops of CellFood dissolved in 0.15l of purified water, or juice, 3 times per day— once during physical activity. The second group (Control group C) took 7% saline solution and citrus artificial flavoring in original packaging to mimic the acidic taste of Cellfood. Both groups started with the procedure the day after the initial measurement and finish after 5 weeks. The second measurement was one day after the last day of supplementation. Statistical Analyses Descriptive statistics included mean, standard deviation and Student`s t-Test for matched pairs (p value of < 0.05). Results Both groups demonstrated improvement in maximum power and VO2 max. In CF group the improvement was statistically significant (p = 0.01) in maximal power and VO2 max, in the other hand, the control group showed statistically significant improvement (p = 0.01) in VO2 max but not in maximal power. Lactate level and maximal hart rate were not statistically significant changed in both groups after 5 weeks of training Discussion Both groups showed similar trends of changes (maximal power, VO2 max, maximal lactate level) but more statistically significant improvements/changes are observed in the CF group (maximal power (p = 0.01), VO2 max (p = 0.01) and lactate level (p = 0.01) compared with the control group (VO2 max (p = 0.05). Based on this preliminary study results we cannot reject hypothesis that Cellfood is beneficial to the adaptation process for the period of 5 weeks training of highly trained (international level) cyclist. The mechanisms of the changes and the effect of Cellfood on adaptation will be the subject of future studies. References 1. Hamilton L et all. J Sports Sci., 2002 Dec;20(12):1001-8 2. Bentley DJ et all. Sports Med. 2007;37(7):575-86 3. Wasserman K.et all.,JAP, 1986;60:2020-27